Nonlinear discrete elements in electro-thermal model of thick film multilayer structure - Błąd, Grzegorz; Klepacki, Dariusz; Potencki, Jerzy (Видавництво Національного університету “Львівська політехніка”, 2005)
Комплексність механізму теплообміну і складності під час визначення коефіцієнтів процесу роблять тепловий аналіз однією з важливих проблем при розробці електронних приладів. Насправді тільки числові методи і спеціальні програми моделювання можуть розв’язати системи диференціальних рівнянь з ускладненими крайовими і початковими умовами. Наведено кілька аспектів опису теплової моделі товстоплівкових мікросхем з еквівалентними моделями на базі RC елементів.

The complexity of heat exchange mechanisms and difficulties in accurate determination of their coefficients make the thermal analysis a complicated problem at the beginning of the design process. In reality, only numerical calculations and specialised simulation programs can solve the systems of differential equations with very complicated boundary and initial conditions. The paper presents some aspects of describing of thermal model of the thick-film microcircuits with equivalent models (based on RC elements).